2012
DOI: 10.1016/j.bbmt.2012.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Antidonor Alloantibody Does Not Indicate Lack of Immune Sensitization: Studies of Graft Loss in a Haploidentical Hematopoietic Cell Transplantation Swine Model

Abstract: Loss of chimerism is an undesirable outcome of allogeneic hematopoietic cell transplantation (HCT) after reduced-intensity conditioning. Understanding the nature of cellular and humoral immune responses to HCT after graft loss could lead to improved retransplantation strategies. We investigated the immunologic responses after graft loss in miniature swine recipients of haploidentical HCT that received reduced-intensity conditioning. After the loss of peripheral blood chimerism, antidonor cellular responses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In our previous studies using similar mild conditioning protocols for hematopoietic cell Tx in swine, we found that in vitro MLR responses did not correlate well with donor kidney graft acceptance . Data generated using this same ITC conditioning protocol in swine suggest that exposure to donor cells using this novel conditioning protocol results in robust, stable immune modulation of donor‐specific antibody responses together with transient immunomodulation of T cell responses ( and unpublished data). The mechanism of immunomodulation mediated by allogeneic cells in this model is unrelated to HSC engraftment.…”
Section: Discussionmentioning
confidence: 76%
“…In our previous studies using similar mild conditioning protocols for hematopoietic cell Tx in swine, we found that in vitro MLR responses did not correlate well with donor kidney graft acceptance . Data generated using this same ITC conditioning protocol in swine suggest that exposure to donor cells using this novel conditioning protocol results in robust, stable immune modulation of donor‐specific antibody responses together with transient immunomodulation of T cell responses ( and unpublished data). The mechanism of immunomodulation mediated by allogeneic cells in this model is unrelated to HSC engraftment.…”
Section: Discussionmentioning
confidence: 76%
“…In mice, central deletional tolerance and peripheral regulatory mechanisms have been shown to control allo-immune responses [33][34][35][36]. Because donor T cells are not depleted and host T cells are partially and transiently depleted in this large animal model [24,25,37], unlike the complete donor and host T cell depletion that can be achieved in rodent studies, we speculate that immune regulatory T cell mechanisms are involved in controlling both donor antihost and host antidonor responses [30,38]. We are currently exploring the mechanism of immunoregulation in this model.…”
Section: Discussionmentioning
confidence: 99%
“…CML assays were performed as previously described [24,25]. Briefly, responders (4 × 10 5 cells) and stimulators (4 × 10 5 cells; irradiated with 25 Gy) were cultured together for 5 days.…”
Section: Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The CD3e-IT-mediated transient chimerism, instead, facilitated the robust and stable humoral immune modulation of donor-specific antibody responses. (44) Treg infiltration into an allograft has been reported in a miniature swine model, suggesting a potential local regulatory component. (4) Nevertheless, the survival and roles of Tregs in CD3e-IT-mediated tolerance induction remain unclear.…”
Section: Introductionmentioning
confidence: 99%